2019
DOI: 10.1021/acs.iecr.9b00499
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Structural Differences between Alkaline and Kraft Lignins by HSQC NMR

Abstract: Technical lignins, mostly generated as byproducts from the pulping industry, are highly abundant aromatic sources. However, they are underutilized due to their complexity, as well as structural alteration during chemical pulping processes. In-depth elucidation of technical lignins is becoming essential for their valorization in view of the lack of understanding of technical lignin structures. In this work, alkaline and kraft lignins were prepared and comparatively characterized by 2D HSQC NMR. By applying auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 43 publications
5
68
0
Order By: Relevance
“…As illustrated in Table , Zhao et al. reported severe structural modifications of the spruce and eucalyptus lignins during alkali extraction process, induced by the depletion of β‐O‐4 linkages and the appearance of aryl enol ether moieties …”
Section: Structural Characteristics Of Various Ligninmentioning
confidence: 99%
“…As illustrated in Table , Zhao et al. reported severe structural modifications of the spruce and eucalyptus lignins during alkali extraction process, induced by the depletion of β‐O‐4 linkages and the appearance of aryl enol ether moieties …”
Section: Structural Characteristics Of Various Ligninmentioning
confidence: 99%
“…To elucidate the structural evolution of KL, both of KL and D Me KL were characterized by X‐ray photoelectron spectroscopy (XPS), [ 32 ] 2D heteronuclear single quantum coherence (HSQC) NMR, [ 23,33,34 ] quantitative 31 P NMR, [ 35–37 ] headspace gas chromatography (HS‐GC), [ 38 ] UV–vi spectrum, [ 39 ] gel permeation chromatography (GPC) and element analysis. The XPS C1s spectra in Figure 1c indicate that, after demethylation and solvolysis, the conjugated carbon with sp2 hybridization and carbon–oxygen double bond increases from 65.1% and 1.87% to 72.9% and 3.28%, respectively.…”
Section: Preparation and Characterization Of Biomass‐derived Dmeklmentioning
confidence: 99%
“…[15c] Therefore alkali lignin of eucalyptus can have up to 12.7 % of resinol structures. [12] In this work, alkali lignin of eucalyptus was used for phenolation study with focus on resinol structures of the lignin.…”
Section: Nmr Characterization Of Phenolated Eucalyptus Ligninmentioning
confidence: 99%
“…[11] Moreover, the structures of β-β are relatively stable in alkaline pulping process and remain significantly as reported that resinol structures of a alkali lignin from eucalyptus was 12.7 %. [12] Therefore, it is interesting and significant to determine how the resinol (β-β) structures of lignins are transformed during an acid-catalyzed phenolation. Reported here is an investigation using syringaresinol and pinoresinol as model compounds to understand the reaction products involving resinol structures in lignins under sulfuric acid catalyzed phenolation conditions.…”
Section: Introductionmentioning
confidence: 99%